Analisis Kebutuhan Sumber Daya Manusia Di Tempat Pendaftaran Pasien Rawat Jalan Rumah Sakit Universitas Sumatera Utara - Yudica Rosalina; Eni Siswanti (Journal of Innovative and Creativity (Joecy), 2025)
Workload analysis is an effort to calculate the workload on a work unit by adding up all workloads and then dividing it by the individual work capacity per unit of time. The type of research used in this study is descriptive with a qualitative approach, the descriptive research method is a research method that aims to provide an objective picture of a situation. In this study, the researcher conducted a descriptive study of the process in the outpatient registration section of the University of North Sumatra Hospital. Qualitative research methods are research methods used to research natural object conditions where the researcher is the key instrument, data collection techniques are carried out triangulation (combination), data analysis is inductive, and the results of the study emphasize meaning rather than generalization. Qualitative research obtains data based on field conditions experienced by participants/data sources. The research design used in this study is phenomenology. With a phenomenological design, researchers try to find out the meaning of an event for people who experience or are in that situation. The subject of the study is an object, thing, or person who has information to be used as a research variable. Based on the results above, it can be seen that the obstacle from the method factor is that the existing SOP still does not cover all the service procedures for the method factor in registration. The number of outpatient registration officers available at the University of North Sumatra Hospital is 4 core outpatient registration officers. Based on the results of the registration officer estimates above, the appropriate number of registration officers is 6 people, so an additional 2 more people are needed